The use of virtual clinics in the management of fractures: a narrative review. Issue 6 (November 2020) - Hickey, Benjamin; Nambiar, Mithun; Onggo, James Randolph; Whitty, Mark; Bedi, Harvinder; Hau, Raphael
Abstract : Virtual fracture clinics (VFC) involve the management and follow-up of appropriate patients through virtual interaction, namely telephone or teleconference consultation and review of imaging. VFCs appear safe for the management of several minor orthopaedic injuries in adults and children. In adults, there is evidence for using a VFC to manage patients with clavicular isolated radial head (Mason 1 and 2), radial neck, and radial styloid fractures, and closed soft-tissue and bony injuries of the hand (excluding carpal and wrist fractures). Stable ankle fractures and fifth metatarsal fractures also can be managed effectively according to VFC protocols. In children, home-based management with VFC review appears effective in management of stable metacarpal, phalangeal, and wrist fractures (undisplaced or torus) and elbow fractures (for children aged over 5 yr). Pediatric metatarsal and lateral malleolar fractures (in patients over 5 yr of age) also can be managed through a VFC.